Analisis Persediaan untuk Menentukan Profit dan Tingkat Pelayanan dengan Metode Simulasi - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2017)
Research analysis of inventory to determine profit and service level in company X with simulation methods is very important to be done to determine the average profit, minimum profit, maximum profit, and service levels with demand uncertainty, which will occur at the company X, which is located in Pegangsaan 2, Kelapa Gading Permai, North Jakarta. The research objective with this simulation method is useful in the near future to determine the possibility of profit that happens, and the service level provided to customers. The long-term goal is to teach the way of solving the problem in inventory in operations management, which is taught in management courses at Bunda Mulia University. Results of this study in operations management were adequate for the subject of inventory, as the company can only provide a service level of 85%. However, the company has gained an average excellent daily profit of Rp 26.474.673. The result can be more effective and efficient if the company uses a planning software to plan and calculate raw materials inventory to satisfy daily customer’s demand.Keywords: Inventory, Simulation, Average profit